Access to timely formal dementia care in Europe - Kerpershoek, Liselot (2020)
The project is supported through the following funding organizations under the aegis of JPND - www.jpnd.eu. Germany, Ministry of Education and Research, Ireland, Health research board, Italy, Ministry of Health, the Netherlands, The Netherlands organization for Health Research and Development, Sweden, The Swedish Research Council for Health, Working Life and Welfare, Norway, The Research Council of Norway, Portugal, Foundation for Science and Technology, (Fundação para a Ciência e Tecnologia (FCT - JPND-HC/0001/2012), United Kingdom, Economic and Social Research Council. JPND has read and approved of the protocol of the Actifcare study.